On Fantasy’s Transmediality: A Cognitive Approach - Rebora, Simone (Comparatismi, 2016)
Books but also movies, TV-series, fanfictions, role-playing games, and much more. The fantasy narrative genre shows one of the highest levels of transmediality. This paper proposes an explanation of the phenomenon, combining the worldbuilding theory with three different approaches in the field of cognitive science. Referring to Gallese’s embodied simulation, the transportation in the Tolkienian “Secondary Worlds” invites a progressive refinement of the fictional universe, allowing multiple media to support its configuration—while also improving personal cognitive skills. In terms of Clark’s extended mind, then, the peculiar involvement stimulated by this type of creations incites a proactive approach to the reading experience, widening it through different tools—while also saturating the possible extensions of the imaginative space. At the same time, these processes can induce insidious addictive dynamics (usually related to the subject’s proneness to excessive daydreaming, but also to the general characteristics of children’s imagination), reinforced by marketing strategies which multiply the cognitive approaches. The theoretical discourse will be supported by narratological analyses of best-seller fantasy novels such as those by Rowling, Martin and Meyer. Some empirical testing will be provided by readers’ reviews on the Goodreads web community, confirming a possible connection between transmediality, narrative transportation and addiction in fantasy fiction.